Efficacy of Chinese herbal medicine in the treatment of anxiety and depression in male sexual dysfunction: a systematic review and meta-analysis protocol - Xie, Zhaozhan; Zhang, Xuecheng; Jia, Hongling; Zhang, Yongchen (Frontiers in Psychiatry, 2025)
BackgroundMale Sexual Dysfunction (MSD), comprising erectile dysfunction (ED), premature ejaculation, and hypoactive sexual desire disorder, exhibits an age-related prevalence affecting 50% of males beyond their fourth decade. Epidemiological studies demonstrate ED prevalence rates of 79.4% in general clinical populations. Beyond physiological manifestations, MSD with comorbid anxiety and depression exerts profound psychosocial impacts, potentially exacerbating pre-existing mental health conditions and impairing interpersonal relationships. Emerging evidence suggests Chinese Herbal Medicine (CHM) may offer therapeutic potential for addressing this clinical intersection. Therefore, this study will perform a systematic review and meta-analysis to assess the efficacy of various CHM interventions for MSD patients with comorbid anxiety and depression.MethodsThis study will systematically search four Chinese databases (China National Knowledge Infrastructure, Wanfang Database, China Biomedical Database, and VIP Database) and four international databases (PubMed, Web of Science, EMBASE, and Cochrane Library). Randomized controlled trials (RCTs) investigating CHM interventions for MSD with comorbid anxiety and depression will be identified. The retrieved studies will undergo rigorous screening and quality assessment using standardized tools.ResultsThe findings of this investigation will establish an evidence-based foundation for optimizing CHM therapeutic protocols in managing MSD with comorbid anxiety and depression.ConclusionsThis investigation will synthesize evidence-based data to evaluate therapeutic outcomes of various CHM modalities for MSD with comorbid anxiety and depression. Through comparative effectiveness analyses, the study aims to establish hierarchical treatment recommendations, enabling clinicians to optimize intervention strategies and facilitate personalized treatment selection in clinical practice.Clinical trial registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD420250652254